Commons, Piracy and the Crisis of Property - James Arvanitakis; Martin Fredriksson (tripleC: Communication, Capitalism & Critique)
This article takes the politicisation of copyright and file sharing as a starting point to discuss the concept of the commons and the construction of property. Empirically, the article draws on a series of interviews with Pirate Party members in Sweden, Australia, Germany, the UK and USA; placed in the theoretical framework of the commons. We argue that piracy, as an act and an ideology, interrogates common understandings of property as something self-evident, natural and uncontestable. Such constructions found liberal market ideology. The article has two broad aims: to outline the different phases of enclosure, from the physical commons, to the institutional and finally the cultural commons; and to discuss the way that piracy highlights the emergent crisis in private property rights, brought to the fore by the global financial crisis and ongoing privatization of public resources. We conclude by questioning what new modes of enclosure are emerging in a digital economy driven by excessive data mining and centralized streaming services.